Prevalence of extended spectrum beta lactamase and AmpC beta lactamase producers among Escherichia coli isolates in a tertiary care hospital in Jaipur - Sinha Parul; Sharma Rajni; Rishi Suman; Sharma Raman; Sood Smita; Pathak Deepali (Wolters Kluwer Medknow Publications, 2008)
Resistance to broad spectrum β lactams, mediated by extended spectrum beta lactamase (ESβL) and AmpC βL enzymes is an increasing problem worldwide. Presence of these in clinical infections can result in treatment failure if one of the second or third generation cephalosporins is used. Therefore, it is recommended that any ESβL-producing organism according to the National Committee for Clinical Laboratory Standards (NCCLS) criteria can be reported as resistant to all extended spectrum β lactam antibiotics regardless of the susceptibility test results. In this study, a total of 250 Escherichia coli (E. coli) isolates were subjected to Double disc test and AmpC disc test for the detection of ESβL- and AmpC βL-producing strains, respectively. Prevalence of ESβL- and AmpC βL-producing strains among E. coli isolates, over a 3-month-period in the hospital-based population of Jaipur, was 64.80% (162/250). AmpC βL producers were 24.00% (60/250) and co-existence of ESβL and AmpC βL was detected in 8.00% (20/250) of the isolates.